Advances in the visual analysis of social movements - Doerr, Nicole; Mattoni, Alice, 1978-; Teune, Simon (Research in social movements, conflicts, and change ;, 2013)
This special issue of Research in Social Movements, Conflicts and Change highlights the importance of visuals in the current study of social movements. It is indispensable reading as it introduces new analytical concepts and methodological frameworks for understanding visuals in social movements; combining cultural and political analysis in a fresh, unique and interdisciplinary way. The articles featured in this special issue examine visual expressions of social movements through case studies from across the globe; including: injustice symbols in the Egyptian uprising; contested images from anti-surveillance protests in Germany; gendered visualization of local activism; commemorative videos of activists in recent European protests; and images used in Australian movements against abortion. In the open section of the volume articles examine the work of renowned political science scholar Charles Tilly, and discuss classic concepts in social movement studies. Firstly, considering the concept of "repertoire of contention" in order to understand the use of distinct contentious performances in Latin America. Secondly, analyzing the role of "storytelling" in the construction of trust and blame in social movements.